Power System Stability Enhancement Using Different Facts Devices: A Review - Kamarudin, Muhammad Nizam; Ab Ghani, Mohd Ruddin; Mohd Shah, Hairol Nizam; Kamis, Zalina (faculty of sciences and technology of the University of El Oued (Algeria), 2018)
Since the beginning of last century,power system stability has been recognized as important problem for secure system operation.Power system instability has causing many major blackouts.The revolution in researches for the minimize power system instability has been attempting a long time ago.This paper represents a review on method used to control power system stability.The techniques presented are compared at each based technique to optimize the control variables for optimization of power system stability.The analysis on performance of the previous work such as disadvantages and limitation of a robust method approach in each technique are included in this paper.The improvement of new approach in each technique depends on the lack,limitation and the results which are expected from the work.